Optimisation design of a steering system based on E-HAM algorithm. (2017) - Zhou, Guan; Zhao, Wanzhong; Duan, Libin; Wang, Chunyan; Chen, Guoping
Owing to the limitation of production cost, the idle shake problem is very common among minivans. To improve the performance of the steering system while keeping the cost not increased, an enhanced hybrid and adaptive meta-model based global optimisation (E-HAM) is applied in this work. Based on the HAM algorithm, the new important region update method (IRU) and different sampling size strategies are integrated in the E-HAM. The resulting precision, convergence rate and search efficiency are improved remarkably. The minivan steering system is then optimised by another six optimisation algorithms to perform the comparisons. Finite element method (FEM) analysis and experiment are also conducted to verify the effectiveness. The results show that the structures are optimised successfully by the E-HAM optimisation method and the idle shake problem is well solved. The research in this work also serves a good example for other structure optimisation problems.